Advances in functional genomics for investigating salinity stress tolerance mechanisms in cereals - Shelden, Megan C.; Roessner, Ute (Frontiers in Plant Science, 2013)
Abiotic stresses such as low water availability and high salinity are major causes of cereal crop yield losses and significantly impact on sustainability. Wheat and barley are two of the most important cereal crops (after maize and rice) and are grown in increasingly hostile environments with soil salinity and drought both expected to increase this century, reducing the availability of arable land. Barley and wheat are classified as glycophytes (salt-sensitive), yet they are more salt-tolerant than other cereal crops such as rice and so are good models for studying salt-tolerance in cereals. The exploitation of genetic variation of phenotypic traits through plant breeding could significantly improve growth of cereals in salinity-affected regions, thus leading to improved crop yields. Genetic variation in phenotypic traits for abiotic stress tolerance have been identified in land races and wild germplasm but the molecular basis of these differences is often difficult to determine due to the complex genetic nature of these species. High-throughput functional genomics technologies, such as transcriptomics, metabolomics, proteomics and ionomics are powerful tools for investigating the molecular responses of plants to abiotic stress. The advancement of these technologies has allowed for the identification and quantification of transcript /metabolites in specific cell types and/or tissues. Using these new technologies on plants will provide a powerful tool to uncovering genetic traits in more complex species such as wheat and barley and provide novel insights into the molecular mechanisms of salinity stress tolerance.